AJAX and JavaServer Faces - Geary, David M. (Prentice Hall, 2007)
Based on material from the forthcoming second edition of Core JavaServer Faces by David Geary and Cay Horstmann, this short cut explores how to use JavaServer Faces and AJAX (Asynchronous JavaScript with XMLHttpRequest) to create rich user interfaces. Starting with a brief review of Ajax fundamentals, it goes on to cover Implementing Ajax with a servlet in a JSF application Using JSF phase listeners for more complex Ajax scenarios Form completion and real-time validation Accessing UI view state from an Ajax call Client-side state saving and Ajax Direct Web Remoting with DWR Finally, after concisely explaining JSF components that wrap existing JavaScript components using Prototype, Scriptaculous, Dojo, and Rico, this Short Cut briefly explores how to use the Ajax4jsf framework to seamlessly integrate Ajax into JSF applications.